Habitual Routines and Automatic Tendencies Differential Roles in Alcohol Misuse Among Undergraduates - Wyckmans, Florent; Chatard, Armand; Saeremans, Mélanie; Kornreich, Charles; Jaafari, Nemat; Fantini-Hauwel, Carole; Noël, Xavier (Frontiers in Psychology, 2020)
There is a debate over whether actions that resist devaluation (i.e. compulsive alcohol consumption) are primarily habit- or goal-directed. The incentive habit account of compulsive actions has received support from behavioral paradigms and brain imaging. In addition, the self-reported Creature of Habit Scale (COHS) has been proposed to capture inter-individual differences in habitual tendencies. It is subdivided into two dimensions: routine and automaticity. We first considered a French version of this questionnaire for validation, based on a sample of 386 undergraduates. The relationship between two dimensions of habit and the risk of substance use disorder and impulsive personality traits was also investigated. COHS has good psychometric properties with both features of habits associated with alcohol consumption and an Obsessive-Compulsive Inventory score. The propensity to rely more on routines was associated with lower levels of alcohol abuse and nicotine use, suggesting that some degree of routine might act as a protective factor against substance use. In contrast, a high automaticity score was associated with an increased risk of harmful alcohol use. These results demonstrate that the COHS is a valid measure of habitual tendencies and represents a useful tool for capturing inter-individual variations in drug use problems in undergraduates.